Fabrication of Calcite Calcium Carbonate from Eggshells Biogenic Waste Through Carbonation Method - Mariyam, Mariyam; Sunarintyas, Siti; Yuliatun, Leny; Khuzaimah, Ismi; Nuryono, Nuryono (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Calcium carbonate derived from eggshells has significant potential for use in drug delivery systems, pharmaceutical, food, catalyst, cement, and concrete industries. Although eggshell waste is non-toxic, its excessive accumulation in the environment may contribute to ecological issues. Colonizing pathogenic bacteria in unprocessed eggshell waste poses a potential health risk. The present study outlines the production of precipitated calcium carbonate (PCC) from eggshell waste through a calcination-carbonation process, offering a sustainable approach to its utilization. The calcination was carried out at 900 ºC. The carbonation process was performed in an HNO3 solution, and the NH3 solution was under-treated for 60 minutes. The results exhibited that the precipitated calcium carbonate (PCC) had a purity of 95.2% CaO. It possessed predominantly the calcite phase with a rhombohedral crystal system, as confirmed by the XRD analysis. The crystallite size of PCC was 109.5 nm, measured using the Debye-Scherrer equation. The phase composition of PCC was 99.3% calcite, 0.5% vaterite, and 0.2% aragonite. FTIR analysis further corroborated this data by showing a sharp and unsplit peak at 1419 cm-1, demonstrating the presence of a calcite phase. SEM images revealed a cubic-like morphology, a characteristic of the calcite form of calcium carbonate (CaCO3). The synthesized calcium carbonate in this study holds potential for applications in dental materials and as fillers in polymer matrices for food packaging.